Primary eosinophilic gastrointestinal disorders and allergy: Clinical and therapeutic implications. Issue 5 (23rd May 2022) - Rossi, Carlo Maria; Lenti, Marco Vincenzo; Merli, Stefania; Licari, Amelia; Votto, Martina; Marseglia, Gian Luigi; Di Sabatino, Antonio
Abstract: Primary eosinophilic gastrointestinal disorders (EGID) are increasingly prevalent, immune‐mediated, chronic conditions which primarily affect pediatric and young adult patients, leading to substantial disease burden, and poor quality of life. EGID may either involve single portions of the gastrointestinal tract (i.e., esophagus, stomach, small bowel, and colon) or a combination. Their strong association with allergic disorders has been recently recognized, and although their shared pathophysiological basis remains partly elusive, this feature greatly impacts the diagnostic and treatment work‐up. We herein critically discuss the current knowledge on the association of EGID and allergic disorders, including atopic dermatitis, allergic rhinitis, allergic asthma, and food or drug allergy. In particular, we reviewed the literature focusing on their epidemiology, pathophysiological basis and mechanisms, and diagnostic strategies. Finally, we discuss the currently ongoing clinical trials targeting EGID and allergic diseases, including, among others the monoclonal antibodies dupilumab, mepolizumab, benralizumab, and lirentelimab.